Effect of caloric restriction and statins on the process of cholesterol transfer to HDL in women with premature CAD. (25th November 2020) - Leal, D.P; Tavoni, T.M; Kawabara, K.L; Faria, N.F.O; Nascimento, J.R.O; Cesar, L.A.M; Strunz, C.M.C; Mansur, A.D.P
Abstract: Introduction: Transfer of cholesterol to HDL from the other lipoprotein classes has an important role in HDL metabolism and function. Patients with premature CAD showed reduced rates of cholesterol transfer, which was not dependent on HDL-cholesterol levels. The effects of statin treatment and caloric restriction on anti-atherogenic properties of HDL, which are critical issues in CAD prevention, have been scarcely described. Purpose: To evaluate the effect of caloric restriction associated or not with statin use on the transfer of cholesterol to HDL. Methods: This randomized study analyzed the functionality of HDL in 26 women, aged ≤55 years, with CAD diagnosed angiographically. Patients were allocated in two groups: caloric restriction (CR) group (n=13) characterized by a diet that reduced 30% of their usual daily caloric intake, and CR plus atorvastatin (CR+A) group (n=13) characterized by the addition of 80 mg of atorvastatin daily to the CR diet. Blood samples were collected before and 60 days after starting interventions for analysis of lipid profile that included apoA-I and B, and to evaluate the anti-atherogenic functionality of HDL by the cholesterol transfer to HDL assay performed in vitro, using artificial donor lipid nanoparticles resembling lipoproteins labeled with radioactive lipids and incubated with total plasma. Results: Body mass index reduced in both groups (p<0.01). In the CR group, we observed a tendency of reduction of total cholesterol from 229±55 to 207±59 mg/dL (p=0.07), LDL-C from 143±40 to 129±49 mg/dL (p=0.07) and HDL-C 56±13 to 53±14 mg/dL (p=0.07). Apo B and apo A-I reduced, respectively, from 1.20±0.35 to 1.05±0.36 g/L (p=0.01) and 1.59±0.32 to 1.43±0.28 g/L (p=0.01). In the CR+A group, we observed reduction of total cholesterol from 253±97 to 169±47 mg/dL (p<0.01), LDL-C from 147±57 to 97±39 mg/dL (p<0.01), and apo B from 1.26±0.39 to 0.85±0.22 g/L (p<0.01). HDL-C and apo A-I did not change. In CR group, the transfers of unesterified and esterified cholesterol to HDL did not change. In CR+A group, the percentage of transfer of unesterified cholesterol to HDL increased by almost 10%, from 3.4±0.6% to 3.7±0.7% (p=0.03), but no change in esterified cholesterol transfer. Conclusion: CR and atorvastatin treatment was not only beneficial because of LDL-C lowering but also by increasing the transfer of unesterified cholesterol to the HDL fraction, an independent anti-atherogenic mechanism, that may be important in the treatment of women with premature CAD. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Brasil (CAPES) – Finance Code 001